Management of Handling Deviant Student Behavior Through Innovation of the Gerbat (Inner Movement) Program: A Study at Srondol Wetan 2 Public Elementary School, Semarang City (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
Objective: The purpose of this study is to describe and analyze the planning, organization, implementation, and evaluation of the management of student deviant behavior through the Gerbat (Inner Movement) program innovation at Srondol Wetan 2 Public Elementary School, Semarang City. Method: The research approach used was qualitative. This type of research is phenomenological. The qualitative research design consists of three stages: orientation, focused exploration, and data analysis. Data collection techniques included interviews, observation, and documentation. This study used source triangulation. Data analysis with three steps: data reduction, data presentation, and drawing conclusions. Results: The results of the study indicate that: 1) Planning is carried out by forming a team, identifying deviant behavior, conducting direct observation of student case records and SOPs integrating spiritual, emotional, and psychological approaches. 2) Organization is carried out by considering personality competencies, concern for students, and experienced teachers. Then forming the Inner Movement Team, school organizational structure and holding training and workshops. 3) Implementation is carried out by implementing the Heart Movement (spiritual) by habituating religious values, praying together, self-reflection, and strengthening moral values. The Emotional Movement (emotional) by habituating empathy, positive communication between teachers and students. The Mind Movement (psychological) with a dialogical approach, simple counseling by teachers and BK teachers. 4) Supervision is carried out by daily and weekly monitoring of changes in student behavior. Follow-up is carried out by improving coaching strategies, adjusting SOPs, mentoring students, and training teachers. Novelty: This research is novel in its approach, namely the application of deviant behavior management through the Gerakan Batin program, which is based on the internalization of spiritual and moral values.